2006
DOI: 10.1103/physrevc.74.034310
|View full text |Cite
|
Sign up to set email alerts
|

Excited states and signature inversion inCs116

Abstract: Excited states have been observed for the first time in the very neutron-deficient, odd-odd nucleus, 116 55 Cs 61 . The assignment to 116 Cs has been made by the detection of γ rays in coincidence with evaporated charged particles and with evaporation residues. The observed states form a rotational band which has been assigned to the ν(h 11/2 ) ⊗ π (h 11/2 ) configuration. Tentative spin assignments have been made on the basis of systematic comparisons with neighboring cesium isotopes. A low-spin signature inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…The data for 114−126 Cs are taken from Refs. [3,17,21,22,[37][38][39][40][41] with spin assignments from Ref. [42].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data for 114−126 Cs are taken from Refs. [3,17,21,22,[37][38][39][40][41] with spin assignments from Ref. [42].…”
Section: Discussionmentioning
confidence: 99%
“…In the neighboring heavier odd-odd cesium isotopes 114,116,118 Cs, decay from the lowest observed state in the most intense rotational band to the ground state is not observed. This is presumably due to the low detection efficiency for low-energy transitions with the apparatus used [20][21][22]. In 120 Cs, decay of the 10 + yrast band-head proceeds to the ground state by multiple low-energy, low-intensity transitions which were observed through the use of low-energy photon (LEPS) detectors [18].…”
Section: A Level Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The recent spectroscopic studies of cesium nuclei have been focused on chirality, which was observed in a long sequence of odd-odd nuclei from 122 Cs to 132 Cs [1]. The odd-even Cs nuclei have been the object of investigations devoted to the evolution of the collective properties far from stability [2][3][4][5][6][7][8][9][10][11][12]. However, the study of the lightest Cs nuclei is confronted with the increasing difficulty to populate high-spin states using fusion-evaporation reactions, due to the limited choice of projectile-target combinations and the small cross sections for neutron evaporation close to the proton drip-line.…”
Section: Introductionmentioning
confidence: 99%
“…The lightest odd-odd nucleus in the Cs chain with a known rich band structure is 120 Cs, in which five band structures have been observed [3,4]. In the lighter 112,114,116,118 Cs nuclei only one rotational structure has been identified, built on the π h 11/2 ⊗ νh 11/2 configuration [5][6][7][8]. The lightest odd-odd Cs nucleus with known spectroscopic information is the proton emitter 112 Cs [9,10], in which five firm and two tentative transitions have been identified and assigned to the π h 11/2 ⊗ νh 11/2 configuration based on systematics [5].…”
Section: Introductionmentioning
confidence: 99%